Treatment exposures stratify need for echocardiographic screening in asymptomatic long-term survivors of hematopoietic stem cell transplantation. (12th February 2019) - Rotz, Seth J.; Powell, Adam; Myers, Kasiani C.; Taylor, Michael D.; Jefferies, John L.; Lane, Adam; El-Bietar, Javier A.; Davies, Stella M.; Dandoy, Christopher E.; Ryan, Thomas D.
Abstract: We sought to define the prevalence of echocardiographic abnormalities in long-term survivors of paediatric hematopoietic stem cell transplantation and determine the utility of screening in asymptomatic patients. We analysed echocardiograms performed on survivors who underwent hematopoietic stem cell transplantation from 1982 to 2006. A total of 389 patients were alive in 2017, with 114 having an echocardiogram obtained ⩾5 years post-infusion. A total of 95 patients had echocardiogram performed for routine surveillance. The mean time post-hematopoietic stem cell transplantation was 13 years. Of 95 patients, 77 (82.1%) had ejection fraction measured, and 10/77 (13.0%) had ejection fraction z-scores ⩽−2.0, which is abnormally low. Those patients with abnormal ejection fraction were significantly more likely to have been exposed to anthracyclines or total body irradiation. Among individuals who received neither anthracyclines nor total body irradiation, only 1/31 (3.2%) was found to have an abnormal ejection fraction of 51.4%, z-score −2.73. In the cohort of 77 patients, the negative predictive value of having a normal ejection fraction given no exposure to total body irradiation or anthracyclines was 96.7% at 95% confidence interval (83.3–99.8%). Systolic dysfunction is relatively common in long-term survivors of paediatric hematopoietic stem cell transplantation who have received anthracyclines or total body irradiation. Survivors who are asymptomatic and did not receive radiation or anthracyclines likely do not require surveillance echocardiograms, unless otherwise indicated.